2007
DOI: 10.1007/s00431-007-0594-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β-cell function in diabetic Taiwanese children using a 6-min glucagon test

Abstract: This study evaluates the effects of glucagon 30 mug/kg (maximal 1 mg) on beta-cell function in children by C-peptide determined before and 6 min after intravenous administration. From 1990 to 2005, 118 Taiwanese children with newly diagnosed diabetes mellitus (98 children with type 1 and 20 children with type 2) and 29 normal Taiwanese children were enrolled in this study. Fasting and 6-min post-glucagon C-peptide levels were analyzed. In the pre-pubertal group, the median fasting serum C-peptide levels were 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(22 reference statements)
2
16
0
Order By: Relevance
“…This is in contrast to Ludvigsson et al who identified that a C‐peptide > 1.0 nmol (equivalent to postprandial UCPCR of 1.8 nmol/mmol) at diagnosis has a predictive value of 46% (1 in 2.1 chance) to discriminate type 1 from non‐type 1 diabetes . This supports other studies in children where C‐peptide at diagnosis was shown to discriminate type 1 from type 2 diabetes with sensitivity varying from 83 to 95% . The metabolic presentation of patients may determine the variable sensitivities of C‐peptide reported in these studies because glucotoxicity at diagnosis may give an artificially low C‐peptide result .…”
Section: Discussionsupporting
confidence: 73%
“…This is in contrast to Ludvigsson et al who identified that a C‐peptide > 1.0 nmol (equivalent to postprandial UCPCR of 1.8 nmol/mmol) at diagnosis has a predictive value of 46% (1 in 2.1 chance) to discriminate type 1 from non‐type 1 diabetes . This supports other studies in children where C‐peptide at diagnosis was shown to discriminate type 1 from type 2 diabetes with sensitivity varying from 83 to 95% . The metabolic presentation of patients may determine the variable sensitivities of C‐peptide reported in these studies because glucotoxicity at diagnosis may give an artificially low C‐peptide result .…”
Section: Discussionsupporting
confidence: 73%
“…and 97% (95% CI 86-100%) and 86% (95% CI 76-93%) in patients with a duration of diabetes >2 years. Furthermore, in Taiwanese patients with childhood-onset type 1 diabetes, Tung et al 10 reported that median fasting serum CPR level was 0.2 nmol/L (0.6 ng/mL) at disease onset. Based on these data, we decided to use 'fasting serum CPR <0.6 ng/mL' as a definition of endogenous insulin deficiency.…”
Section: Cut-off Level For Endogenous Insulin Deficiencymentioning
confidence: 99%
“…Other studies in children have shown that C-peptide at diagnosis could differentiate T1DM from T2DM with sensitivities varying from 83 to 95% [20,21,22]. Katz et al [21] demonstrated that a C- peptide level of 0.85 ng/ml had a sensitivity of 83% and a specificity of 89%.…”
Section: Discussionmentioning
confidence: 99%